ROLE OF CYCLiC NUCLEOTiDE SiGNAL SYSTEMS iN REGULATiON OF iMMUNOAND PATHOGENESiS - O. V. Yurieva (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
Modern data concerning functional regularities of the secondary signal systems of cyclic nucleotides (CN) in immune and. pathological reactions of a macroorganism, are analyzed, in this review. Intracellular regulatory mechanisms controlling CN system, and. its interaction with other signal systems are described. Influence of endogenic and. exogenic factors on activity of CN system, components and. its use as means or «targets» of special exposure to immune and. pathological reactions of a macroorganism, are examined.